Juvenile Systemic Sclerosis: Review of 17 Portuguese Patients. Issue 2 (May 2017) - Sousa, Sandra; Fernandes, Susana; Estanqueiro, Paula; Zilhão, Carla; Resende, Catarina; Aguiar, Francisca; Brito, Iva; Oliveira-Ramos, Filipa; Salgado, Manuel; Guedes, Margarida; Melo-Gomes, José; Santos, Maria J.
Introduction: Juvenile systemic sclerosis (jSSc) represents about 10% of all systemic sclerosis patients. We aim to describe the clinical characteristics and disease progression of children with jSSc followed in Portuguese pediatric rheumatology centers. Methods: Clinical and laboratory features as well as medication and outcomes of jSSc children were reviewed. Results: Seventeen patients were included in the analysis, 5 of whom had overlap syndromes. Thirteen girls, with a mean age at diagnosis of 10.6 ± 3.9 years and mean disease duration of 10.5 ± 3.9 years, of these 12 had diffuse cutaneous scleroderma. In 94% cases, the first symptom was Raynaud's phenomenon (RP), followed by arthritis and/or puffy hands (59%). Pulmonary involvement was documented in 7 patients at disease diagnosis, despite the paucity of respiratory complaints. Thirteen patients presented periungual capillaropathy. During follow-up, RP and skin thickening were the most frequent clinical manifestations (100%), followed by arthralgia (94%) and arthritis (76%). Pulmonary, as well as gastrointestinal involvement was documented in eight patients. Sixteen children were antinuclear (ANA) positive, eight tested positive for anti-Scl70, and one for anti-fibrillarin antibodies. Immunosuppressants (94%), proton pump inhibitors (76%) and glucocorticoids (65%) were the most common therapeutic options. One child needed autologous bone marrow transplant due to severe refractory disease. An improvement of skin thickening and stabilization of pulmonary involvement was documented in most cases. No deaths were registered in this cohort. Conclusions: Raynaud's phenomenon as well as capillaroscopic abnormalities were almost universal at disease presentation. Internal organ involvement was common and occurred early during disease course, although asymptomatic in several cases.